SUMBER KONFLIK DAN POTENSI PENERAPAN ALTERNATIF PENYELESAIAN KONFLIK (APK) DALAM SENGKETA LINGKUNGAN HIDUP(Conflict Sources and the Potential of Alternative Dispute Resolution (ADR) Application on Environmental Conflict: The Case of Sasorladang Community) - Tua Hasiholan Hutabarat (Jurnal Manusia dan Lingkungan, 2004)
ABSTRAKPenelitian ini mengkaji konflik lingkungan yang terjadi antara masyarakat Porsea dengan PT. Inti Indorayon Utama (IIU). Konflik ini terjadi berkepanjangan karena tidak bertemunya faktor-faktor rasional dan irasional. Penelitian ini bertujuan mengkaji bagaimana faktor-faktor yang irasional bekerja dalam penyelesaian konflik melalui Altemative Dispute Resolution (ADR). Penelitian ini menggunakan metodologi deskriptif melalui survai baik dengan kuesioner maupun interview. Penelitian ini menemukan bahwa dari 4 faktor rasional yang dipertimbangkan dalam penyelesaian konflik hanya faktor penerimaan bantuan yang berkorelasi dengan pengembangan sikap masyarakat. Adapun faktor-faktor irasional memiliki relasi, dan faktor etnosentrik manjadi faktor yang paling berpengaruh. ABSTRACTThis research was carried out based on an environmental conflict phenomenon between Porsea people, especially Sosorladang, and PT Inti Indorayan Utama or Toba Pulp Lestari (PT IIU/TPL). Occurred four years, the conflict is difficult to resolve due to some irrational factors aside from rational ones that should have made the conflict resolution realistic. The research aims to identify how the nonrealistic conflict influences an unfeasibility of solution through an approach of Alternative Dispute Resolution (ADR). The method used was a combination of survey and descriptive approaches. The main means of data collection questionnaire supported by in-depth interview and direct field observation, including the company environment. Data derived from questionnaire and interview were analyzed by examining their correlation. The result of the correlation test show that among four rational factors considered, only aid acceptance factor that has relation in building up the societal attitude. The irrational factors prove a real relationship, and the ethnocentric factor become the most influential factor. It is proven that the conflict between the inhabitant and company is due to a nonrealistic factor.